(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article defines such an important component of finance on the global, macroeconomic, regional and territorial levels as climate finance, analyzes their structure and mechanism of their operation, offers solutions to environmental problems in Ukraine by improving financial instruments taking into account the world experience. In the XXIst century, humanity has entered a new stage of development that can be called a turning point in terms of environmental impact of man on nature. Scientists warn that further warming of the planet even by one degree by Celsius could lead to additional air pollution by 55 billion tons of carbon by 2050. This can lead to the fatal processes in the climate system of the Earth and passing by our planet an environmental point of no return. Therefore it is important now to develop the set of measures within the ecological system of economy to stop these processes, including the financial plan. That’s why the financial system in each country has to allocate such a part as climate finance, through which influence on the suspension of global warming on the planet could be more effective. The analysis of foreign and Ukrainian literature on the above stated issues allows us to offer the scientific community to discuss the following definition of climate finance. This is a set of financial instruments, tools, rules and regulations that promote the conservation and improvement of environmental conditions for the proper reproduction of the inputs and sustainable development in the scale of the world and the groups of countries as well at the country level, its region, a separate territorial community. In some developed countries, an important part of climate finance are now becoming some elements of households (fines for improper waste handling, extra income from excess electricity production and its transmission to the territorial electricity grids etc.). That’s why it is advisable to develop a system of special incentives (mainly tax incentives) to encourage sponsors and patrons to invest in projects improving the climate of social reproduction at all levels: from global level to microlevel. The structure of climate finance in current conditions should include such financial instruments as environmental taxes, incentives and penalties, as well as investments and loans to improve the climate conditions of reproduction of the inputs at all levels (international, within a particular state, region or community). Climate finance should also include leverage, tools, norms and standards directed against those entities (states, transnational companies, individual countries, individuals) that affect climate at all levels (internationally, within a particular country, its regions, certain communities). First of all, it concerns the influence of international community on the actions of transnational companies (TNCs), that are widely not complying climate reproduction conditions, are violating environmental standards of production in developing countries.